Implementation of Just-in-sequence concept in automotive industry – comparation of Austrian and Serbian model - Anđelković, Aleksandra M (Industrija, 2017)
Strong competition and increasing demands from customers continuously encourage companies from the automotive industry to improve its processes. Jist-in-time as one of the strategies of managing inventory, which is applied 40 years ago in the automotive industry; represent a great support to many companies, particularly Japanese, for achieving a competitive position in the market. However, implementation of Just-in-sequence approach could be used for minimizing the disadvantages of Just-in-time strategy. Author use comprehensive analysis of literature for explaining Just-in-sequence approach. Comparing Just-in-time and Just-in-sequence approach author points to the differences between them. Empirical research shows a level of implementation Just-in-sequence approach in two automotive clusters (one from Republic of Austria and one from Republic of Serbia). Explaining reasons for selecting clusters from these countries, with the use of appropriate statistical methods, author points to the differences between samples.